Factors Causing Pending Medical Record Claims For Inpatients At Tidar Public Hospital Magelang - Yeni Tri Utami; Tominanto Tominanto; Dita Amalina Sari (Proceeding of International Conference on Science, Health, And Technology, 2022)
A pending claim is a claim that is returned by the BPJS Health verifier to the hospital for revision which will later be resubmitted. This study aims to determine the factors causing pending claims at Tidar Hospital, Magelang City 2021. This research is a descriptive study, with a retrospective approach. The sample is 805 claim files that have pending claims using the saturated sample technique. The research instrument was interview guide and observation guide. Data processing with classification, editing, and data presentation in the form of text and tabulation. The implementation of BPJS claims at Tidar Public Hospital, Magelang has been implemented and has implemented the existing SOPs. The classification of pending BPJS claims for inpatients at Tidar Public Hospital, Magelang, includes: Coding, Clinical, and Administrative. The causes of pending claims for medical records of inpatients at Tidar Public Hospital, Magelang, among others, are because the Man element is an officer related to the implementation of claims, Material is the completeness of the claim requirements file, and Machine is the supporting facilities and infrastructure in the service. The claim implementation at Tidar Public Hospital, Magelang, has been carried out in accordance with the existing SOP, but there are still files that are returned by BPJS for repairs because the Coding, Clinical, and administrative aspects are caused by Man, Material, Machine factors. The author suggests that coding training should be held for special officers for BPJS claims, Conducted socialization of Incomplete Filling of Medical Records (KLPCM) to Medical Personnel who collaborate with medical records to improve quality and reduce the impact of pending claims due to clinical aspects, It is advisable to update the system to reduce the impact of systems that often have errors and slow networks because they can interfere with hospital service activities.